Analysis Of The Influence Of Beauty Influencer Tasya Farasya's Attitude On Consumer Purchase Intention Through Consumer Attitude Towards Influencer As a Mediator - Annisa Fitriany Sabrina Mirza; Agus Abdurrahman (Cita konsultindo, 2024)
This research is research that examines the relationship between the attitude of beauty influencer Tasya Farasya and consumer purchase intention which is mediated by consumer attitudes towards Influencers. This research aims to identify the influence of influencer attitudes which include the dimensions of credibility, trustworthiness, expertise, liking, similarity, familiarity and attractiveness which are mediated by attitudes towards influencers in influencing consumer purchase intention. This research uses a quantitative approach using primary data in the form of a questionnaire as a research data collection tool. The data in this research was processed using SEM (Structural Equation Modeling) with the help of AMOS to test the research hypothesis. This research produces findings that attitudes towards influencers can mediate the positive and significant influence of beauty influencer Tasya Farasya's attitude on consumer purchase intention. The results of this research provide important insights for marketers and social media practitioners in understanding how attitudes towards influencers, especially in terms of credibility, trustworthiness, expertise, likeability, similarity, familiarity and attractiveness, can influence consumer purchasing interest.